Erbjudanden om barns meningsskapande i lärarledda aktiviteter i fritidshem - Hedrén, Sanna; Hjalmarsson, Maria (Utbildning & Lärande, 2025)
This study explores children’s meaning-making based on observations of teacher-led activities within Swedish School-Age EduCare (SAEC). SAEC exists in a tension between discourses of voluntariness and governance. Its mission is to provide children with a meaningful leisure experience. But how can teacher-led activities, influenced by both of these discourses, become meaningful for children? And how can teachers contribute to children’s meaning-making during SAEC activities? The observed teacher-led activities are analyzed using conceptualizations of meaning-making and affordance. The results reveal three different aspects of meaning-making: intentional, situated, and relational. Additionally, the findings highlight teachers’ opportunities to make activities meaningful for children at the situated and relational levels, even if the activity itself does not inherently attract the child.